Developmental Pharmacogenetics of CYP2D6 in Chinese Children: Loratadine as a Substrate Drug - Li, Qian; Wu, Yue-E; Wang, Kai; Shi, Hai-Yan; Zhou, Yue; Zheng, Yi; Hao, Guo-Xiang; Yang, Yi-Lei; Su, Le-Qun; Wang, Wen-Qi; Yang, Xin-Mei; Zhao, Wei (Frontiers in Pharmacology, 2021)
Objective: The elucidation of CYP2D6 developmental pharmacogenetics in children has improved, however, these findings have been largely limited to studies of Caucasian children. Given the clear differences in CYP2D6 pharmacogenetic profiles in people of different ancestries, there remains an unmet need to better understand the developmental pharmacogenetics in populations of different ancestries. We sought to use loratadine as a substrate drug to evaluate the effects of ontogeny and pharmacogenetics on the developmental pattern of CYP2D6 in Chinese pediatric patients. Methods: Chinese children receiving loratadine treatment were enrolled in the present study. The metabolite-to-parent ratio (M/P ratio), defined as the molar ratio of desloratadine to loratadine of trough concentrations samples at steady-state condition, was used as a surrogate of CYP2D6 activity. Loratadine and desloratadine were determined by LC/MS/MS method. Variants of CYP2D6 were genotyped by polymerase chain reaction for CYP2D6 *4, *10, *41 and long polymerase chain reaction for CYP2D6 *5. Results: A total of 40 patients were available for final analysis. The mean age was 4.50 (range 0.50–9.00) years and the mean weight was 19.64 (range 7.00–42.00) kg. The M/P ratio was significantly lower in intermediate metabolizers (IMs) compared to normal metabolizers (NMs) (10.18±7.97 versus 18.80±15.83, p = 0.03). Weight was also found to be significantly associated with M/P ratio (p = 0.03). Conclusion: The developmental pharmacogenetics of CYP2D6 in Chinese children was evaluated using loratadine as a substrate drug. This study emphasizes the importance of evaluating the developmental pharmacogenetics in populations of different ancestries.